Blockchain-Enabled Secure Data Sharing for AI-Driven Applications: Privacy and Efficiency Trade-offs (Journal of Artificial Intelligence & Research, 2024)
The rapid advancement of artificial intelligence (AI) technologies has led to an increased demand for secure and efficient data sharing practices. This paper examines the role of blockchain technology in enabling secure data sharing for AI-driven applications, with a focus on privacy and efficiency trade-offs. By utilizing blockchain's decentralized nature, it becomes possible to mitigate data leakage risks and enhance trust in sensitive sectors such as healthcare and finance. This study explores how blockchain can be leveraged to create secure data-sharing environments, ensuring compliance with regulatory requirements while maintaining the efficiency needed for AI algorithms. Key challenges and potential solutions in integrating blockchain with AI are discussed, alongside real-world applications and future research directions.